INTEGRASI DISCOVERY LEARNING BERBANTUAN PPT INTERAKTIF TERHADAP KETERAMPILAN PROSES SAINS PESERTA DIDIK SEKOLAH DASAR - Dhea Anisya Putri; Profithasari, Nindy; Erni; Khairani, Fadhilah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of discovery learning integration assisted by interactive PPT on science process skills in elementary school students. The approach used in this study is quantitative with the Quasi-Experimental Design method. The research design uses Nonequivalent Control Group Design. The population in this study was all grade VI at SDN 1 Sukadana Baru, totaling 46 students. The sampling technique used saturated sampling. Data collection techniques used tests in the form of essay questions and non-tests in the form of observation sheets. The prerequisite test for data analysis used normality, homogeneity, and hypothesis testing, namely simple linear regression tests. The results showed that F count = 17.405 with a significance of 0.001, which means 0.001 <0.05 so that H0 was rejected and Ha was accepted, it can be concluded that there is an effect of discovery learning integration assisted by interactive PPT on science process skills.